Incorporating insurance provisions in microfinance contracts: Learning from Visa®? - Loïc Sadoulet (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
We examine a simple extension to existing credit contacts for the poor (`microfinance contracts'), that would allow financial institutions to provide repayment insurance to their clients. The proposed contract uses the repeated nature of loans to build credit records that borrowers in good standing can use to insure themselves against default in case of adverse income shocks. After documenting borrowers' desire for insurance using data from a microfinance programme in Guatemala, we derive sufficient conditions for the proposed contract to reduce borrower vulnerability while improving repayment rates. These conditions are quite similar to those that credit-card and automobile-insurance companies seem to apply to deter moral hazard and adverse selection among their subscribers. We close the paper with a discussion on why institutions lending to the poor may face particular implementation problems because of the history of past failures of credit programmess for the poor. – microfinance ; insurance ; reputation
Keywords: O17; G20; G22; D82; 330; Kreditversicherung; Reputation; Guatemala; Mikrofinanz